SDSS-IV MaNGA: properties of galaxies with kinematically decoupled stellar and gaseous components - Jin, Yifei; Chen, Yanmei; Shi, Yong; Tremonti, C.A.; Bershady, M.A.; Merrifield, M.; Emsellem, E.; Fu, Hai; Wake, D.; Bundy, K.; Lin, Lihwai; Argudo-Fernandez, M.; et al. (Oxford University Press, 2016)
We study the properties of 66 galaxies with kinematically misaligned gas and stars from MaNGA survey. The fraction of kinematically misaligned galaxies varies with galaxy physical parameters, i.e. M*, SFR and sSFR. According to their sSFR, we further classify these 66 galaxies into three categories, 10 star-forming, 26 ‘Green Valley’ and 30 quiescent ones. The properties of different types of kinematically misaligned galaxies are different in that the star-forming ones have positive gradient in Dn4000 and higher gas-phase metallicity, while the green valley/quiescent ones have negative Dn4000 gradients and lower gas-phase metallicity on average. There is evidence that all types of the kinematically misaligned galaxies tend to live in more isolated environment. Based on all these observational results, we propose a scenario for the formation of star-forming galaxies with kinematically misaligned gas and stars \-− the progenitor accretes misaligned gas from a gas-rich dwarf or cosmic web, the cancellation of angular momentum from gas–gas collisions between the pre-existing gas and the accreted gas largely accelerates gas inflow, leading to fast centrally concentrated star formation. The higher metallicity is due to enrichment from this star formation. For the kinematically misaligned green valley and quiescent galaxies, they might be formed through gas-poor progenitors accreting kinematically misaligned gas from satellites which are smaller in mass.